A busca do corpo ideal: consumo de rotinas de beleza e saúde, constituição da identidade e questões de gênero - Hage, Zakiee Castro Mufarrej (2022)
The culture of beauty permeates contemporary society and imposes beauty and health care routines that reach a wide audience, at different stages of the life cycle, but with a view to maintaining youth. Despite the social pressure for a perfect body and health involving several groups, the literature addresses with more emphasis the struggle waged by women to achieve this ideal. Thus, our objective was to investigate, from the perspective of the constitution of identities, the routines of care adopted with the body and the meanings attributed to it by women in the adult phase of the life cycle. The research, anchored in systemic theory, was developed through mixed methods. The initial phase, quantitative, allowed to map the consumption of beauty and health routines among 146 participants, through an online questionnaire. In the qualitative phase, 30 women who had more intense care routines were selected, as well as women with less intense care, in order to compare the extremes, to answer a semi-structured interview, in order to unravel the meanings attributed to this care. In the quantitative phase, some issues stood out: body satisfaction among women appears to 59.1% of the collaborators. Problems related to weight and the performance of physical exercises are preponderant, representing the reality of almost 60% of the interviewees, who mostly affirm the regular use of cosmetics and aesthetic treatments, equivalent to 80% of the sample. Qualitative analysis did not indicate differences in care between groups of women, but highlighted the importance of an external look at the body, the social demands for maintaining youth and beauty, and the privilege of thinness as a body style to be achieved. The narrative of women between 55 and 64 years old indicated a need to fight the signs of aging and rescue youth. It was concluded that the gaze of the other, even in the face of the critical gaze of highly educated women, affects identities and the way in which these women perceive themselves